Stress levels in bulls during and after electroejaculation - Md Khair, Mohd Faiz; Yusoff, Rosnina; Omar, Mohamed Ariff; Haron, Abdul Wahid (2011)
The Animal Welfare Society has expressed its concern on the use of electroejaculator as a semen collection device. The society believes that electroejaculation will incur pain to the animal and thus causing stress. Thus, this will compromise the quality of semen collected from the animal. A study was conducted to observe it bulls were stressed when the electroejaculation technique was applied for semen collection. A serum blood sample was collected before, immediately after and after semen collection using the EE technique. Changes in serum cortisol concentration in serial blood samples were used to quantify stress response in the bulbs. Eight bulls aged from 3 to 8 years and weighing between 320 and 830 kg were randomly assigned to one of the two treatments. The first treatment group consisted of bulls that were inserted with a probe and given electrical stimuli (ES) while the second treatment group comprised of bulls that were inserted with a rectal probe but without electrical stimulus (WES). Blood samples were collected by venipuncture at rest (first before the rectal probe was inserted), immediately after ejaculation, 10 and 15 min postejaculation. There was no significant difference (p ≥ 0.05) between the group with electrical stimulus and the group without electrical stimulus. However, there are significant differences between bulls in each group. The use of probe with electrical stimuli did not significantly increase serum cortisol concentration.